IMMUNOLOGICAL STATUS OF SALMONELLA PULLORUM-INFECTED BROILERS TREATED WITH BACILLUS SUBTILIS, ORGANIC ACIDS AND CIPROFLOXACIN - Abeer I. Abdulwahhab,; M. T. Al-Zuhariy, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The current study was aimed to ascertain the impact of ciprofloxacin, an acidifier acid, and a Bacillus subtilis on immunological function and growth efficiency after a starter-phase challenge with Salmonella pullorum. 250 broiler chicks (Ross 308) were put into five groups of fifty each, all groups except the fifth group, orally challenged with S. pullorum at one day old, and provided with a supplement in drinking water after three days as follow G1: treated with B. subtilis (2×107 CFU/g) (250 g/1000 L). G2: treated with acidifier acid (0.5-1 ml/L). G3: treated with ciprofloxacin 10% (0.5 ml/L). G4: only infected with S. pullorum. G5: control negative. The findings revealed extremely significant variations in the means antibodies (IgG) and IFN-γ titre against Salmonella pullorum in serum which was increased significantly at the level (P≤0.05) in all groups at 7 days, particularly in G4 and G1, in comparison with G5, but, at 21 and 35 days the results of IgG and IFN-γ titers showed a significant decrease (P>0.05), the results of immunity matching with most probable number (MPN/g) of S. pullorum in feces. Additionally, the highest significantly differences at the level (P≤0.05) in growth performance across all groups. We conclusion, the organic acid has biggest role in protection in comparison with ciprofloxacin that have immunosuppression also, the B. subtilis not recorded any protection.